A Simple and Selective Nanocatalytic Resonance Rayleigh Scattering Spectral Method for the Determination of Trace Re - Shengmian Wang; Guiqing Wen; Tingsheng Li; Xianjiu Liao; Aihui Liang; Zhiliang Jiang (Journal of Spectroscopy)
In the HCl medium, rhenium (VII) or Re nanoparticles exhibited strong catalytic effect on the slow Te particle reaction between Te(VI) and Sn(II) at 70°C. The product of formed Te particles shows two strong resonance Rayleigh scattering peaks at 778 nm and 540 nm. The RS intensity at 778 nm enhanced linearly with Re concentration. The enhanced RS intensity was linear Re concentration in the range of 0.01–2.0 nmol·L−1, with a detection limit of 0.005 nmol·L−1 Re. This method was applied to the analysis of Re in ore sample, and the results were in agreement with that of the spectrophotometry.